2003
DOI: 10.1002/jbm.a.10442
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion on supported lipid bilayers

Abstract: The cell and protein repellent properties of supported phospholipid bilayer (SPB) membranes were investigated. The SPBs were prepared by vesicle adsorption on SiO(2) surfaces. The vesicles of phosphatidylcholine fuse and rupture, and form a supported bilayer covering the surface. We carried out cell culture experiments on several surfaces, including SPBs, using two types of epithelial cells to address the cell adhesional properties. The Quartz Crystal Microbalance Dissipation (QCM-D) technique was used to moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
97
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 45 publications
6
97
0
Order By: Relevance
“…non-fouling surface, does not promote protein and cell adhesion [28][29][30][31][32] . The reason for this discrepanc y is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…non-fouling surface, does not promote protein and cell adhesion [28][29][30][31][32] . The reason for this discrepanc y is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the differences is considered due to a surface morphology, that is, fluid-like character or rigid character of the surfaces. Many non-fouling surfaces that resist to cell adhesion had a fluid-like character 32 . On the other hand, super-hydrophilic surface of titanium dioxide films 33 or O 2 -treated HMDSO films that showed a high rate of cell attachment had a rigid surface.…”
Section: Discussionmentioning
confidence: 99%
“…Supported lipid bilayer (SLB), an artificial mimic of the natural cell membrane, which is compatible with protein incorporation and possesses sustained lateral mobility, [20][21][22][23][24][25][26] has been studied extensively as model system of biological membranes over past decades. Previously, many studies have demonstrated that this biomimetic multifunctional material has great bioinert property and lateral mobility, thus leading to effective resistance of non-specific proteins adsorption and cells adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the formation of SLBs is simple 14 and they are highly resistant to nonspecific adsorption by proteins or cells. 12,[15][16][17][18] SLBs consist of a continuous lipid bilayer, 5 nm thick, separated from the substrate by a ϳ1 nm thin water cushion. Previous studies of cell adhesion with SLBs have relied on the use of lipids functionalized with peptides.…”
Section: Introductionmentioning
confidence: 99%